RETRACTED: Effect of pretreatment temperature on catalytic performance of the catalysts derived from cobalt carbonyl cluster in Fischer-Tropsch Synthesis - O, Byambasuren; D, Ulziibayar; D, Chiibaatar (Mongolian Journal of Chemistry, 2017)
On 3rd March 2018, the Editorial Board of the Mongolian Journal of Chemistry decided to retract the article entitled "Effect of pretreatment temperature on catalytic performance of the catalysts derived from cobalt carbonyl cluster in Fischer-Tropsch Synthesis" because of an authorship dispute. The article was originally published in Vol.17 No.43 2016 pp.38-41. DOI: http://dx.doi.org/10.5564/mjc.v17i43.745